Effect of superdosing phytase on productive performance and egg quality in laying hens - Kim, Jong Hyuk; Pitargue, Franco Martinez; Jung, Hyunjung; Han, Gi Ppeum; Choi, Hyeon Seok; Kil, Dong Yong (Animal bioscience, 2017)
An experiment was conducted to determine the effect of superdosing phytase on productive performance and egg quality in laying hens. A total of 200 42-wk-old Hy-Line Brown laying hens were allotted into 1 of 5 dietary treatments with 5 replicates consisting of 8 hens per replicate. The positive control (PC) and negative control diets (NC) were prepared based on the recommended P levels in layer diets. Supplemental phytase was added to the negative control diet at 10,000 (SD10), 20,000 (SD20), or 30,000 (SD30) fytase units (FTU)/kg. Productive performance was summarized for 6 weeks from 42 weeks to 47 weeks of age. Egg quality was assessed from 4 eggs per replicate randomly collected at the conclusion of the experiment. The SD20 treatment had greater (p<0.05) hen-day egg production than PC, NC, and SD10 treatment groups. There was no difference in hen-day egg production between SD20 and SD30 treatment groups. However, SD30 treatment had greater (p<0.05) hen-day egg production than PC treatment, but showed no difference in hen-day egg production as compared to NC and SD10 treatment groups. However, egg weight, egg mass, feed intake, and feed conversion ratio were not affected by dietary treatments. Egg quality including eggshell strength, eggshell color, egg yolk color, and haugh unit was not influenced by dietary treatments. Superdosing level of 20,000 FTU/kg phytase in diets has a positive effect on egg production rate, but no beneficial effect on egg quality in laying hens.